IMPROVING STUDENTS’ PROFICIENCY IN TEACHING FOR ENGLISH SPECIFIC PURPOSE - Daulay, Ernita; Septian Nasution, Sukma; Rahmawati, Rahmawati (VISION, 2024)
ESP focuses on practical communication skills directly applicable to students’ chosen careers. This can include learning to read and write reports, engaging in constructive discussions, or delivering clear presentations. By connecting English language learning with students’ future professional or academic goals, ESP enhances learning motivation, resulting in significant improvements in all language skills, including grammar, vocabulary, reading comprehension, and speaking fluency. This study will investigate ideas, beliefs, and practices relating to extrasensory perception (ESP) by the gathering and examination of many literature sources, such as books, papers, scientific journals, and other electronic sources (Syukur & Nugraha, 2019). The point of this paper is to address the complexities of current ESP instruction. To begin with, we offer an outline of changes that have happened in ESP instruction over the past few decades. Moreover, highlights the developing significance of needs investigation.